Simulasi Sistem Dinamis Bahan Pangan Tambahan Guna Pemenuhan Kebutuhan Konsumen dan Peningkatan Keuntungan Petani - Yuli Dwi Astanti; Reiza Novita Putri; Laila Nafisah (OPSI, 2022)
Shallots (Allium cepa var ascalonicum L.) is one of the most popular food additives in Indonesia. These ingredients are used to add flavor to Indonesian cuisine. The increase in community needs caused by the increase in population has an impact on increasing the demand for shallots every year. This increase also occurred in Bantul Regency. The demand for shallots in Bantul is not accompanied by a balance in the amount of supply obtained from shallot-producing areas. This is because most farmers in Bantul Regency only plant shallots in the dry season. Therefore, this study seeks to propose how to balance the supply of shallots by farmers with market demand to increase farmers' profits. This study uses a dynamic system simulation approach with the help of Powersim studio 9 software. The first step is to build a Causal Loop Diagram (CLD) to see the causal or reciprocal relationship between variances and stock-flow diagrams to compile a mathematical formulation of the system model. dynamic. The simulation results are then validated to determine the credibility of the model. After the model is declared valid, 3 (three) scenarios of implementing the strategy in the shallot supply chain model will be generated. The best model scenario simulation results are scenario 1 (one), namely by replacing the use of tuber seeds in all activities.